GNSS-RO investigation of tropopause dynamics surrounding the geomagnetic storm of 10–13 May 2024 - Gautam, Tulashi; Paudel, Madhu Sudan; Ghimire, Basu Dev; Chapagain, Narayan Prasad (BIBECHANA, 2026)
The tropopause is the transitional layer between the troposphere and stratosphere, which has its significance in the weather monitoring and forecasting, aviation technology, and other various fields. GNSS-RO is a method that is widely used to study and understand the atmospheric properties and the phenomena related to it. In this study, the atmospheric data from the Constellation Observing System for Meteorology Ionosphere and Climate – 2 (COSMIC-2) mission are used to understand the impact of geomagnetic storm from 10-13 May 2024 on the tropopause parameters. The tropopause height (TRH) and tropopause temperature (TRT) is calculated using the World Meteorological Organization 1957 (WMO 1957) criteria during, before and after the geomagnetic storm time as well as on the same days in previous years. The result obtained is compared to each other. During the geomagnetic storm time, global variation of TRH with longitude shows almost constant nature in tropical region (0o to ~23o latitude) and higher-latitude (> 35o) region but sharp changes is observed in sub-tropical region (~23o to ~35o latitude). The increase in TRH can be seen in tropical region when compared to prior years, might be due to global increase in temperature in 2024 in May. Analysis of the period of 10-13 May 2024, reveals no significant increase in TRH in tropical region compared to the period from May 26-29, 2024. But, at sub-tropical and higher latitude, TRH has found to be increased in southern hemisphere in the period with geomagnetic storm. This seems to show that the geomagnetic storm may have impacted the global TRH and TRT at sub-tropical and higher latitude region, while no any effect is observed in tropical region.